Study on the molecular mechanism of matrine in improving rheumatoid arthritis by targeting the NAV2-Wnt3a/β-catenin axis to coordinately regulate the inflammatory-osteolytic loop - Guo, Qianyu; Liang, Meie; Li, Zhen; Li, Jie; Xu, Ke; Zhang, Liyun (Frontiers in Immunology, 2025)
BackgroundThe occurrence and development of rheumatoid arthritis (RA) are closely related to bone erosion caused by the abnormal activation of the Wnt3a/β-catenin signaling pathway. However, it remains unclear how natural products target and regulate this pathway at the molecular level. This study focuses on the role of the novel neuronal guidance protein NAV2 in RA and systematically analyzes the immunoregulatory mechanism of matrine (MAT).MethodA Wistar rat model of type II collagen-induced arthritis (CIA) was established by co-induction with bovine type II-collagen and Freund’s adjuvant. Twenty-four rats were randomly divided into four groups in total: a normal control group (NOR), a model group (CIA), a methotrexate treatment group (MTX), and a matrine treatment group (MAT). Intragastric administration was carried out over four weeks.Ankle bone mineral density (BMD), trabecular thickness (tb.th) and other related indicators were detected. The dynamic balance of serum inflammatory factors was measured via enzyme-linked immunosorbent assay (ELISA). The destruction of articular bone was gauged utilizing three-dimensional reconstruction with Micro-CT. Hematoxylin and eosin (HE) staining, along with O-fast green staining, were employed to appraise synovial inflammation and the degree of cartilage damage in the joints. qRT-PCR and Western blotting were utilized to detect the mRNA and protein expression levels of NAV2, Wnt3a, and β-catenin in rat joints.ResultMAT remarkably decreased the arthritis index in CIA rats (p<0.01), and effectively ameliorated articular bone erosion and synovial inflammatory infiltration. MAT systematically reduced the levels of pro-inflammatory cytokines, while increasing the levels of anti-inflammatory cytokines. No significant statistical differences were observed in liver and kidney function between the MAT group and NOR group (p>0.05). MAT significantly inhibited the mRNA and protein expressions of NAV2, Wnt3a, and β-catenin in joints (all p<0.05). Following intervention with MAT, there was a significant decrease in the positive areas of these three molecules (p<0.01).ConclusionThrough the targeted inhibition of the NAV2-Wnt3a/β-catenin signal transduction pathway, MAT exerts a dual-regulatory effect to restore the equilibrium of the inflammatory cytokine network. Moreover, MAT demonstrates no hepatotoxicity or nephrotoxicity, thereby providing a novel candidate molecule and a mechanistic target for the intervention of autoimmune diseases using natural drugs.